ПЕРМСКИЕ ДВУСТВОРЧАТЫЕ МОЛЛЮСКИ ЗАБАЙКАЛЬЯ - Бяков А.С. (My University, 2002)
Permian bivalves of the Transbaikal Region are for the first time treated monographically. Seven biostratigraphic units ranked as beds with fauna are described and correlated with the Permian bivalve zonation for northeastern Asia. All 18 species identified from these units are figured and six new species, Palaeoneilo postolegi, Poudevcia jamesi, P. zabaikalica, Leptodesma indistincta, Streblopteria alenae, and Cyrtorostra nana, are described. Copyright © 2002 by MAIK "Nauka/Interperiodica".
Keywords: ДВУСТВОРЧАТЫЕ МОЛЛЮСКИ; МОЛЛЮСКИ; ЗАБАЙКАЛЬЕ; ПЕРМЬ; Permian; 564.1(571.54/55); Paleozoic::Permian; Палеозой::Пермская